Date palm diverts organic solutes for root osmotic adjustment and protects leaves from oxidative damage in early drought acclimation - Franzisky, Bastian L; Mueller, Heike M; Du, Baoguo; Lux, Thomas; White, Philip J; Carpentier, Sebastien Christian; Winkler, Jana Barbro; Schnitzler, Joerg-Peter; Kudla, Jörg; Kangasjärvi, Jaakko; Reichelt, Michael; Mithöfer, Axel; et al. (Oxford University Press, 2025)
Date palm (Phoenix dactylifera L.) is an important crop in arid regions that is well-adapted to desert ecosystems. To understand the remarkable ability to grow and yield in water-limited environments, experiments with water-withholding for up to four weeks were conducted. In response to drought, root, rather than leaf, osmotic strength increased, with organic solutes such as sugars and amino acids contributing more to the osmolyte increase than minerals. Consistently, carbon and amino acid metabolism was acclimated toward biosynthesis at both the transcriptional and translational levels. In leaves, a remodeling of membrane systems was observed, suggesting changes in thylakoid lipid composition, which together with the restructuring of the photosynthetic apparatus, indicated an acclimation preventing oxidative damage. Thus, xerophilic date palm avoids oxidative damage under drought by combined prevention and rapid detoxification of oxygen radicals. Although minerals were expected to serve as cheap key osmotics, date palm also relies on organic osmolytes for osmotic adjustment of the roots during early drought acclimation. The diversion of these resources away from growth is consistent with date palm's strategy of generally slow growth in harsh environments and clearly indicates a trade-off between growth and stress-related physiological responses.